Is it time to define complete mesocolic excision as a standardized colon cancer surgery? - Wang, Chao; Gao, Zhidong; Shen, Zhanlong; Jiang, Kewei; Wang, Shan; Ye, Yingjiang (Translational Gastroenterology and Hepatology, 2018)
We appreciate that Negoi et al. (1) agree with us on the oncological benefit of complete mesocolic excision (CME) in colon cancer, which is one of the primary objectives of our article (2) and the rationale to advocate the standardization and quality control of colon cancer surgery. The general view of colorectal surgeons is that introduction of total mesorectal excision results in revolutionary improvement in rectal cancer surgery, thereby improving prognosis (3). In contrast, in spite of nearly 10 years since the introduction of CME, its safety and efficiency is controversial (4). This may be owing to the lack of quality control in previous studies. Not all surgeries followed the standards of the CME group, which might affect the confounding factors of prognosis (4).